2007
DOI: 10.1007/s00402-007-0514-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rupture of Achilles tendon: is the percutaneous suture technique effective?

Abstract: Our series is one of the largest to be reported for the treatment of chronic rupture. Our technique offers a considerable advantage; it is minimal invasive, easy to perform with no associated harvesting morbidity and increased patient acceptance. We recommend this technique for the treatment of chronic rupture of Achilles tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Reconstruction of the chronically ruptured Achilles tendon is not free from complications [10,12,29], and Wound breakdown, infection (9%) and DVT are wellknown complications of surgical repair [23,26]. Unfortunately, there were 2 patients with superficial wound infection (18%) and one with DVT (10%) in present study.…”
Section: Discussionmentioning
confidence: 94%
“…Reconstruction of the chronically ruptured Achilles tendon is not free from complications [10,12,29], and Wound breakdown, infection (9%) and DVT are wellknown complications of surgical repair [23,26]. Unfortunately, there were 2 patients with superficial wound infection (18%) and one with DVT (10%) in present study.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, Maffulli et al [43,44] proved that percutaneous repair of Achilles tendon was not only available for diabetic patients but also suitable for patients >65 years. Furthermore, Kosanovic et al [45] showed that percutaneous repair was effective in treating chronic Achilles tendon rupture. In a recent meta-analysis, McMahon et al [46] concluded that percutaneous minimally invasive surgery had a significantly reduced risk of superficial wound infection and a three times larger number of patients with good to excellent results compared with conventional open repair.…”
Section: Discussionmentioning
confidence: 98%
“…14,22 The role of operative and nonoperative treatment in acute ruptures continues to be debated, but some investigators agree that chronic ruptures should be treated operatively unless there are contraindications for surgery or the patient has minimal functional demands. 14,20 The aim of surgery is to restore and maintain the length of the Achilles tendon to achieve propulsive gait by the gastrocsoleus muscle complex. 17,27 Nonoperative treatment should be used for patients who have minimal functional demands, poor healing capacity, high medical morbidity such as uncontrolled diabetes mellitus, or vascular disease; however, increased rerupture rates and decreased functional results are seen with nonoperative treatment.…”
Section: Introductionmentioning
confidence: 99%